Natural Dye Sensitized Photo Electrochemical Cells for Solar Energy Conversion. Issue 2 (20th June 2020) - Shiyani, T; Agrawal, S; Banerjee, I
Abstract : ZnO thin films have been characterized to determine the band edges potential position for photoelectrochemical (PEC) water splitting. Zinc oxide (ZnO) films were fabricated on florin doped tin oxide (FTO) coated glass substrate using sputtering method. Natural dyes were extracted from basil, spinach, pomegranate, thor and sunflower using aqueous method. A layer of natural dye was deposited on ZnO thin film by drop casting method and dried at room temperature for making hybrid photoelectrodes to enhance the performance of PEC device. These hybrid photoelectrode were characterized using structural, optical and photoelectrochemical measurements. PECs were tested for generating photocurrent and photovoltage using a three electrode system in a 0.1 M Na2 SO4 electrolyte. We found that natural dye plays an important role to enhance the performance of hybrid PEC. The dye sensitized PEC has achieved energy conversion efficiency from 0.2-0.7% enhanced by 15-33% due to usage of various natural dye on ZnO. Solar energy conversion using these hybrid photoelectrodes may lead an eco-friendly and cheap way to generate solar fuels in future.